Peran Dipa Nusantara Aidit pada Peristiwa Berdarah G30s Tahun 1965 - Muhammad Ihsan Aulia; Samsudin Samsudin; Widiati Isana (UIN Sunan Gunung Djati Bandung, 2019)
Dipa Nusantara Aidit was a figure in the Indonesian Communist Party since 1947. His role was very important in the events of the G30S in 1965, especially because of his political movements that resulted in the event. This writing aims to determine the biography of Dipa Nusantara Aidit and how the role of Dipa Nusantara Aidit in the G30S incident in 1965. The method used in this study is the historical method. The results of this study Dipa Nusantara Aidit was a communist figure in the Indonesian Communist Party, active in Menteng 31 by establishing Gerindom (Gerakan Indonesia Merdeka) then establishing PBK (Persatuan Buruh Kendaraan), establishing API (Angkatan Pemuda Indonesia), and LEKRA. He once served as CC PKI Secretary General and Deputy Chair of the MPRS. Aidit was also active in writing books, among his works were the History of the Indonesian Workers' Movement, Taking the Way of the Rakya, Towards a New Indonesia, the Birth of the PKI and Its Development, and the Peasants Extending Village Demons. Second, D.N. Aidit in 1953 deposed Alimin and became CC PKI Secretary General through the Plenary Session. Aidit launched various revolutionary offensive from January to September 1965. Aidit through the PKI launched various issues such as forming Force V, Nasakom and the Council of Generals which later became a bloody coup in the kidnapping of generals on October 1, 1965. Although in the end Aidit himself was captured and was killed in Boyolali on November 22, 1965.